Clinical approach to infections in pregnancy (New York Hayle Medical, 2023)
Pregnancy refers to a series and process of changes that occur in a woman's tissues and organs due to the development of a fetus. It causes numerous changes in the body which makes women more vulnerable to various infections. Pregnant women get more severe infections with certain organisms such as hepatitis E virus (HEV), malaria parasites, influenza virus and herpes simplex virus (HSV), than non-pregnant women. Being infected during pregnancy increases the risk of birth defects like blindness or visual impairment, epilepsy, hearing loss and learning difficulties for unborn babies. Antibacterial medications including cephalosporins, penicillins and medicines related to erythromycin are generally regarded as safe to use during pregnancy. This book aims to present a clinical approach to infections in pregnancy. It presents researches and studies performed by experts across the globe. Those in search of information to further their knowledge will be greatly assisted by this book.
Keywords: Medical Science; Gynecology and Obstetrics; Diseases and Complication of Pregnancy; Mitchell, Charlotte ed